Effect of a gas–gas-heater on H2SO4 aerosol formation: Implications for mist formation in amine based carbon capture. (August 2015) - Mertens, Jan; Bruns, R.; Schallert, B.; Faniel, N.; Khakharia, P.; Albrecht, W.; Goetheer, E.; Blondeau, J.; Schaber, K.
Highlights: This study presents the potential of a GGH to minimise amine emissions. A GGH removes up to 70% of sulphuric acid from the flue gas. A GGH prevents the homogenous nucleation of sulphuric acid into aerosols. Information will serve designing future aerosol emission countermeasures. Abstract: This study is to our knowledge the first to describe the effect of a Gas–Gas Heater (GGH) of a coal fired power plant's has on (i) the H2 SO4 concentration and (ii) the particle/aerosol number concentration and particle size distribution present in the flue gas. In the absence of a GGH, homogenous nucleation takes places inside the Wet Flue Gas Desulphurisation (WFGD) converting the gaseous H2 SO4 into aerosol H2 SO4 . This leads to a high aerosol number concentration behind the WFGD with 80% of the aerosols being smaller than 0.02 μm. This implies that an amine based carbon capture (CC) installation treating this flue gas can suffer from amine mist formation due to the high amount of available nuclei (i.e., H2 SO4 aerosols) resulting in high amine emissions. In contrast, in the presence of a GGH not only 70% of the H2 SO4 is removed from the flue gas (measured at the Nijmegen powerplant), but also homogenous nucleation in the WFGD is prevented resulting in low particle number concentrations. The flue gas leaving the GGH will not create any mist formation issues in an amine based CC installation due to the low amount of nuclei present in the flue gas. It is not the reduction in H2 SO4 concentration by 70% inside the GGH as such that prevents mist formation but absence of H2 SO4 in its aerosol form. These results are most likely quite widely transformable to other power plants that burn low sulfur coal i.e., around 0.7 weight%. This information will serve future pilot and demo CC installation around the world; in particular when retrofitted on power plants that have a GGH.